Karakteristik ibu dan pemberian ASI eksklusif dengan kejadian stunting di Kelurahan Padebuolo Kota Gorontalo - Indra Domili; Syafrawati Djamadi Suleman; Fitri Yani Arbie; M Anas Anasiru; Rahma Labatjo (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
Children who do not get exclusive breastfeeding will be at risk of deficiency of nutrients needed in the growth process. This study aims to analyze the relationship between stunting and exclusive breastfeeding. The research method uses a cross-sectional research design with quantitative research, presented by means of descriptive-analytic with the number of respondents as many as 41 people. Data regarding the child's height was obtained by measuring the child's height using a digital weight scale with an accuracy of 0,1 kg. Data regarding children's age is obtained by birth certificate records or family cards. Mothers’ knowledge about exclusive breastfeeding and its giving was obtained using interview techniques. Data analysis using univariate analysis was carried out on each variable resulting from the study in the form of frequency distribution and percentage of each variable. Bivariate analysis to analyze the relationship between variables using Chi-square with 95% CI. The results showed that knowledge (p= 0,633) and education (p= 0,840) had no effect on exclusive breastfeeding (p > 0,05). Meanwhile, exclusive breastfeeding did not affect the incidence of stunting (p= 0,797). In conclusion, education, knowledge and exclusive breastfeeding have no significant correlation with the incidence of stunting in children under five.